Essential oils: from prevention to treatment of skin cancer. Issue 2 (February 2019) - Pavithra, P.S.; Mehta, Alka; Verma, Rama S.
Highlights: The chemopreventive activity of essential oils (EOs) against skin cancer is reviewed. The anti-melanoma and anti-nonmelanoma activity of EOs and EO components is described. EOs and EO components have immense potential as topical therapeutics. Abstract : The increasing incidence of cutaneous malignancies signifies the need for multiple treatment options. Several available reviews have emphasized the potential role of various botanical extracts and naturally occurring compounds as anti-skin-cancer agents. Few studies relate to the role of chemoprevention and therapeutic activity of essential oils (EOs) and EO components. The present review summarizes an overview of chemopreventive, anti-melanoma and anti-nonmelanoma activities of EOs from various plants and EO components in in vitro and in vivo models with special emphasis on skin cancer. Also, the mechanisms by which EOs and EO components exert their effects to induce cell death are presented.